PENGARUH LEVERAGE,UKURAN PERUSAHAAN,ROA,KEPEMILIKAN INSTITUSIONAL, KOMPENSASI KERUGIAN FISKAL, DAN CSR TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN TERDAFTAR DI BEI 2013 – 2015 - Rusli Reinaldo; Zirman '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to examine the impact of Leverage, Company Size, Return On Asset, Institusional Ownership, Compensation Tax Losses and Corporate Social Responsibility against Tax Avoidance on manufacturing companies subsector food and berverages and this research aimed to examine the effect from the independent variables that could be significantly influence or not againt Tax Avoidance. The sample used in this research is based on criteria that have been set and totally amounted 41 manufacturing company that listed on Indonesian Stock Exchange 2013 -2015. This research used purposive sampling method and testing the hypothesis using double linear regression analysis test (Using SPSS 18.0). Result from this research showed that the independent variables return on asset and compensation tax losses significantly influence the partial against tax avoidance and the leverage, company size, institusional ownership and corporate social responsibility has no effect pasrtialy against tax avoidance. Result of coefficient of determination (adjusted R2) of 0,476. This mean that the overall effect of independent variables against tax avoidance amounted 47,6% while the remaining amounted 52,4% is influenced by the other independent variables that not used in this research.Keyword : Tax Avoidance, Return On Asset, Institusional Ownership, Compensation Tax Losses, Corporate Social Responsibility.